HISTORY OF THE EMERGENCE AND SPREAD OF THE SCIENTIFIC TERM "PERSPECTIVE" IN THE THEORY OF IMAGES - Sh. Abdurahmanov; S. Jo'raeva; D. Tursunalieva (American Journals, 2023)
The article states that when the scientific term "Perspective" appeared in the theory of images and was widely spread around the world, the great merit of the work "Book on Optics" by the famous scientist of the East Abu Ali Hassan al Haysam (965 – 1040).
Keywords: drawing tools, geometric constructions, conic sections, optics (the science of vision), pinhole camera